Biodegradable Binder from Natural Resources for Biomass Densification - Yau , Wing Tim (IRC, 2016)
In the world today, it is generally acknowledged that the combustion of fossil fuels is the major source of anthropogenic degradation of the environment. Therefore, it is vital that biomass from plants to be used as an alternative renewable and carbon-neutral raw material for the production of energy. However, wide application of the biomass materials is often restricted by the requirement of pre-treatment processes to increase the bulk density. To increase the bulk density of the biomass feedstock, it is usually compressed into pellets through the densification process. Nonetheless, the production of low quality pellets may result in transportation and storage issues as the dust emitted by those pellets will cause fire and explosion hazards. Therefore, the production of durable pellets requires the need to blend binding agents into the biomass feedstock.